Material didáctico para el desarrollo de las destrezas con criterio de desempeño en el bloque curricular 5 “el ciclo en la naturaleza y sus cambios” en el área de ciencias naturales en las niñas del cuarto año de educación general básica de la escuela Eliseo Álvarez de la ciudad de Loja, período lectivo 2013-2014. Lineamiento propositivo - Fernández Romero, Hugo Arturo (2014)
The present investigation called "TEACHING MATERIALS FOR DEVELOPING SKILLS WITH PERFORMANCE CRITERIA CURRICULUM IN BLOCK 5" CYCLE IN NATURE AND CHANGES "IN THE AREA OF NATURAL SCIENCES IN GIRLS OF FOURTH YEAR OF BASIC EDUCATION GENERAL ELISEO ALVAREZ SCHOOL CITY OF LOJA, LECTIVO PERIOD 2013-2014. GUIDELINE PROACTIVE" aims to determine the causes of the lack of use of Learning Materials. Raised the overall aim of determining the causes of the failure to use Training Material for skill development with performance criterion in the curricular "The cycle of nature and its changes" in the area of Natural Sciences in girls of the fourth year of Basic General Education school "Eliseo Álvarez" city of Loja; as well as specific objectives: Check nonuse of Teaching Materials by teacher Area of Natural Sciences, establish levels of knowledge of the block without the application of teaching materials in girls fourth year of basic general education school Eliseo Álvarez; and develop proactive application-oriented guidelines of teaching material in the curricular "The cycle of nature and its changes" for teachers in the area of Natural Sciences. To develop research has used the scientific method, the inductive method, deductive method, the analytical method, the synthetic method and descriptive method, some techniques were also used as the interview and survey technique applied to teachers and students in General Basic Education School "Eliseo Álvarez" city of Loja, corresponding to 67 students and 2 teachers from the area of Natural Sciences. By applying surveys and analysis thereof has been raised as an alternative guideline a slideshow that cover a range of means and resources that facilitate teaching and learning of science; is to facilitate the acquisition of concepts, skills, attitudes and skills that contribute actively in the teaching-learning process of girls. Through the development of the research proposal it could be concluded that the use of teaching materials within science classes captures the interest of the students and enhances the development of their abilities and skills, which is why using recommended this teaching material in taught by teachers of science content.